Is intensive monitoring during the first transfusion in pediatric patients necessary?. Issue 5 (July 2014) - Berg, Aaron; Courtney, Rachael; Krishnamurti, Lakshmanan; Triulzi, Darrell J.; Yazer, Mark H.
Abstract : Background: Some pediatric patients, typically those that are very young or felt to be especially sick are temporarily admitted to the intensive care unit (ICU) for observation during their first transfusion. If a significant reaction that requires ICU management does not occur, these patients are then transferred to a regular ward where future blood products are administered. The aim of this project was to determine if heightened observation such as temporary ICU admissions for the first transfusion are warranted. Methods: From the blood bank records of a tertiary care pediatric hospital, a list of patients on whom a transfusion reaction was reported between 2007 and 2012, the type of reaction and the patient's transfusion history, were extracted. The hospital location where the transfusion occurred, and whether the patient was evaluated by the ICU team or transferred to the ICU for management of the reaction was determined from the patient's electronic medical record. Results: There were 174 acute reactions in 150 patients. Of these 150 patients, 13 (8.7%) different patients experienced a reaction during their first transfusion; all 13 patients experienced clinically mild reactions (8 febrile non-hemolytic, 4 mild allergic, and 1 patient who simultaneously had a mild allergic and a febrile non-hemolytic), and none required ICU management. Six severe reactions (6 of 174, 3.4%) involving significant hypotension and/or hypoxia that required acute and intensive management occurred during subsequent (i.e. not the first) transfusion in six patients. Conclusions: The practice of intensive observation for the first transfusion in pediatric patients is probably unnecessary.